The Dome of the Rock: An Analysis of Its Origins Kubah Sakhrah: Satu Analisis Asal-usulnya - Omer, Spahic (Journal of Islam in Asia (E-ISSN 2289-8077), 2015)
Abstract This paper challenges an old belief that the Dome of the Rock in Jerusalem was built between 65/684 and 72/691 by the Umayyad caliph ‘Abd al-Malik Ibn Marwān. The paper is divided into two parts. The first part briefly examines the significance of the Rock (Øakhrah). Therein we have shown that the Rock has no special religious significance whatsoever. The second part tries to answer who exactly built the Dome of the Rock and when. The paper concludes that the likely truth is that the caliph ‘Abd al-Malik ibn Marwān was able to commence building the edifice only after crushing the insurgence of ‘Abd Allah ibn al-Zubayr in 73/692. Such were the socio-political conditions in the Muslim state during the insurgency that the caliph’s actions could not transcend the planning and basic preparatory stages, at most. Whether the caliph ‘Abd al-Malik ibn Marwān was capable of completing the structure during his lifetime or not, remained a debatable point as well. The task of building one of the first and at the same time greatest masterpieces in Islamic architecture might have been completed by his son and successor, al-WalÊd ibn ‘Abd al-Malik. What follows is shedding more light on these aspects of the topic. Keywords: The Dome of the Rock, al-AqÎÉ Mosque, the Caliph ‘Abd al-Malik ibn Marwān, the Caliph al-WalÊd ibn ‘Abd al-Malik. Abstrak Kajian ini mencabar kepercayaan lama bahawa Kubah Sakhrah di Yerusalem dibina antara 65/684 dan 72/691 oleh khalifah Umayyah 'Abd al-Malik b. Marwan. Kajian ini dibahagikan kepada dua bahagian. Bahagian pertama menelitikan kepentingan Sakhrah. Dimana kami menunjukkan bahawa Sakhrah tidak mempunyai signifikan agama sekalipun. Bahagian kedua cuba menjawab dengan tepat siapa yang membina Kubah Sakhrah dan bila ia dibina. Kajian ini menyimpulkan bahawa kemungkinan besar khalifah 'Abd al-Malik b. Marwan mampu bermula membina hanya selepas mengalahkan pemberontak daripada 'Abdullah b. al-Zubayr pada 73/692. Begitulah keadaan sosio-politik di negeri Islam semasa pemberontakan sehingga tindakan khalifah tidak dapat mengatasi perancangan dan peringkat persediaan asas. Sama ada Khalifah 'Abd al-Malik b. Marwan mampu menyiapkan struktur semasa hayat beliau atau tidak, ia masih diperdebatkan. Tugas membina salah satu seni bina Islam yang pertama dan yang terunggul mungkin telah disiapkan oleh anak dan penggantinya, al-Walid b. 'Abd al-Malik. Berikutnya mencurahkan lebih banyak keterangan pada aspek topik ini. Kata Kunci: Kubah Sakhrah, Masjid al-Aqsa, khalifah ‘Abd al-Malik b. Marwan, khalifah al-Walid b. ‘Abd al-Malik.